A novel Cd-MOF with enhanced thermo-sensitivity: the rational design, synthesis and multipurpose applications. Issue 12 (12th May 2021) - Ju, Ping; Li, Mengting; Yang, Hua; Jiang, Long; Xia, Lian; Kong, Rongmei; Zhang, Ensheng; Qu, Fengli
Abstract : A novel thermo-sensitive fluorescent Cd-MOF probe (complex 1 ) and its multipurpose sensing properties have been revealed. Abstract : A novel fluorescent Cd-MOF probe [Cd2 (btec)(TPB)0.5 (H2 O)4 ]·2H2 O (complex 1, TPB = 1, 2, 4, 5-Tetra(4-pyridyl)benzene) has been rationally designed and synthesized, and its multipurpose sensing applications have been revealed. The thermo-sensitive property of complex 1 was investigated in a wide temperature range from 20 °C to 160 °C. A good linear relationship was observed between the fluorescence quenching efficiency of complex 1 and the circumstance temperature, which suggested that complex 1 could be a promising material for application in fluorescent thermometers. Stable suspensions could be obtained after dispersion of complex 1 in various solvents, especially in water. A remarkable red shift (about 20 nm) in the fluorescence emission spectrum of complex 1 was observed when H2 O was used as the dispersion medium compared with that in D2 O, which could be used for distinguishing D2 O from H2 O. Furthermore, based on the strong inner filtering effect (IFE), the fluorescence detection of acetone in water was carried out using complex 1 -H2 O suspensions. Real-time fluorescence quenching was observed after the addition of acetone into complex 1 -H2 O suspensions. Moreover, the fluorescence quenching efficiency vs. the concentration of acetone fitted well with a non-linear equation ( R 2 = 0.9929) with an experimental detection limit for acetone as 0.06% (vol%). In addition, the photoelectric responses study revealed that complex 1 might be modified and used as a photoelectric sensor.